2019
DOI: 10.3389/fgene.2019.01080
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Atlas of Gene Expression for the Domestic Goat (Capra hircus)

Abstract: Goats (Capra hircus) are an economically important livestock species providing meat and milk across the globe. They are of particular importance in tropical agri-systems contributing to sustainable agriculture, alleviation of poverty, social cohesion, and utilisation of marginal grazing. There are excellent genetic and genomic resources available for goats, including a highly contiguous reference genome (ARS1). However, gene expression information is limited in comparison to other ruminants. To support functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Overall, the identified DEGs in multiple core tissues between beef and dairy cattle should enable our understanding of their transcriptional regulation on development and functional differentiation of tissue. In addition, our study further supports tissue-specific regulatory patterns which are consistent with the action of natural selection across species, as described in passerine birds [ 110 ], primates [ 111 ], and high-altitude vertebrates [ 112 ], and help to understand the genomic variation and their regulations in diverse breeds that may reflect differences in production traits [ 4 , 27 , 113 ].…”
Section: Discussionsupporting
confidence: 83%
“…Overall, the identified DEGs in multiple core tissues between beef and dairy cattle should enable our understanding of their transcriptional regulation on development and functional differentiation of tissue. In addition, our study further supports tissue-specific regulatory patterns which are consistent with the action of natural selection across species, as described in passerine birds [ 110 ], primates [ 111 ], and high-altitude vertebrates [ 112 ], and help to understand the genomic variation and their regulations in diverse breeds that may reflect differences in production traits [ 4 , 27 , 113 ].…”
Section: Discussionsupporting
confidence: 83%
“…Graphia is a computational tool which enables the analysis and visualization of large correlation networks. Amongst many applications it was used to identify cell and tissue-specific co-expression clusters in the sheep ( Clark et al, 2017 ), pig ( Summers et al, 2019 ) goat ( Muriuki et al, 2019 ), water buffalo ( Young et al, 2019 ), and chicken ( Bush et al, 2018a ) transcriptional atlas projects. Co-expression analysis of a detailed time course of the transcriptomic response of human MDM to LPS treatment based upon sequencing of CAGE (genome scale 5′ RACE) libraries revealed the transient induction of positive and negative regulators ( Baillie et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the brain and the testis exhibited a higher percentage of tissue-enriched proteins, which were also found in human ( UhlĂ©n et al, 2015 ; Wang et al, 2019 ), cattle ( Liu et al, 2020 ), sheep ( Clark et al, 2017 ), and goat ( Muriuki et al, 2019 ), than other organs. The result of the functional analysis showed that brain-enriched genes were significantly associated with synapse and neuron function and testis-enriched genes with spermatogenesis and reproduction in humans ( Wang et al, 2019 ), cattle ( Liu et al, 2020 ), and donkey.…”
Section: Discussionmentioning
confidence: 92%
“…One cattle transcriptome study showed that 16,564 genes were detected by analyzing 100 different tissues and cell types ( Liu et al, 2020 ). In addition, approximately 18,528, 19,921, and 14,426 protein-coding genes were detected in domestic goat ( Muriuki et al, 2019 ), sheep ( Clark et al, 2017 ), and pig ( Freeman et al, 2012 ), respectively. The number of detected genes in donkey is equivalent to that in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation